Sexual Dimorphism in Wing Shape and Its Impact on Conspecific Identification of Neotropical Fannia Species (Diptera: Fanniidae) - Yesica Durango-Manrique; Andrés López-Rubio; Giovan F. Gómez (Taxonomy)
Neotropical species of the genus Fannia remain poorly known despite their potential collection as biological evidence in criminal investigations. This is partly due to taxonomic difficulties and a lack of specialists. Identifying neotropical species of Fannia relies mainly on the classical morphological characters of adult males, as females show high similarity between species. Here, landmark-based geometric morphometrics of the wing could constitute an additional tool for associating adult females with conspecifics in this genus. In this study, we used a reference dataset of males belonging to ten putative species of Fannia from Colombia and molecular data to test this hypothesis. We found a strong wing shape sexual dimorphism, resulting in an almost perfect sex assignment based solely on this trait. However, the differences in wing shape between sexes were greater than those between species, making conspecific identification difficult. Our data show that wing shape could only feasibly be used for identifying adult males and females of F. lamosca, and males of F. dorsomaculata and F. pseudoconstricta. Low discrimination scores among remaining species may be partly explained by high intraspecific variation, slight wing shape differences among closely related species, or sampling bias. Although this study provides the first wing size and shape comparison among neotropical Fannia species, more samples and species are needed to validate these findings and identify the potential factors influencing this trait. Furthermore, the wing shape sexual dimorphism across Fannia species suggests different life-history strategies between sexes and possible genetic canalization mechanisms.